PENGARUH MOTIVASI, PERSEPSI PENDIDIKAN, DAN PELATIHAN TERHADAP PENGEMBANGAN KARIR PEGAWAI DINAS PENDIDIKAN, KEBUDAYAAN, KEPEMUDAAN, DAN OLAHRAGA KABUPATEN SEMARANG - Sholikah, Nanik; Violinda, Qristin; Setyorini, Noni (Bussman Journal : Indonesian Journal of Business and Management, 2025)
This study aims to determine the influence of motivation, perceptions of education, and training on employee career development. The method used was a quantitative approach using survey techniques and multiple linear regression analysis. The results indicate that motivation, perceptions of education, and training each have a positive and significant influence on career development. Employees with high motivation, positive perceptions of education, and who participate in effective training tend to have better career opportunities. These findings confirm that career development is determined not only by organizational structural factors, but also by individual motivation and continuous learning processes.